Analysis of inorganic ions in gingival crevicular fluid as indicators of periodontal disease activity: A clinico-biochemical study - Arati C Koregol; Shobha P More; Sangamesh Nainegali; Nagaraj Kalburgi; Siddharth Verma (Wolters Kluwer Medknow Publications, 2011)
Aim: Gingival crevicular fluid (GCF) is regarded as a promising medium for detection of markers of periodontal disease activity. Very few investigators have examined concentration of electrolytes in GCF, but most results are not in agreement to one another. This study was undertaken with an objective of quantitative estimation of sodium, potassium and calcium concentrations of GCF in gingivitis and periodontitis, to find the reliability of these ions as diagnostic markers and to analyze the relation of these ions to one another. This will indicate stage of disease activity which helps in early diagnosis, prevention and treatment of periodontal diseases. Materials and Methods: The patients selected for the study included both sexes, aging from 18 to 55 years, divided into two groups: gingivitis (group I) and periodontitis (group II). Using volumetric microcapillary pipette, 5 μl GCF was collected for quantitative analysis of sodium, potassium and calcium using flame photometry. Results: The concentrations of sodium, potassium and calcium in GCF and their significant correlation with gingival index and pocket depth measurements reflect the clinical status of gingival and periodontal tissues. Conclusions: Estimation of these electrolytes may be used as potential diagnostic markers of active disease status in periodontal tissues and to predict the effective methods of prevention and treatment.